An integrated system of dielectric barrier discharge combined with wet electrostatic precipitator for simultaneous removal of NO and SO2: Key factors assessments, products analysis and mechanism. (1st June 2018) - Cui, Shaoping; Hao, Runlong; Fu, Dong
Highlights: An integrated system of DBD with WESP for simultaneous removal of NO and SO2 was developed. Effects of Vp-p and O2 /H2 O concentrations on the removal efficiency were illustrated. The removal products of SO2 and NO were determined as sulfate and nitrate. Abstract: This paper developed an integrated system of Dielectric Barrier Discharge (DBD) with Wet Electrostatic Precipitator (WESP) for simultaneous removal of NO and SO2 . In view of practical application, the effects of some key factors such as peak-peak voltage (Vp-p ), O2 and H2 O contents on the simultaneous removal of NO and SO2 were systematically investigated. The results indicated that, in single DBD process, the additions of O2 and H2 O significantly promoted the removal of SO2, especially in presence of Vp-p, but remarkably inhibited the conversion of NO, which was due to the regeneration of NO from the radical-induced reactions among N, O and OH. WESP played a key role in capturing the oxidizing products and acid aerosols, and as anticipated, the integrated system of DBD-WESP showed a better performance on the simultaneous removal of NO and SO2, with the best efficiencies of 98.9% for SO2 and 87.1% for NO. The interaction mechanism among the components in the presence of Vp-p was speculated, the transformations of SO2 and NO in this system were also proposed. The removal products of SO2 and NO by the integrated system were determined as sulfate and nitrate according to the Ion Chromatography (IC) analysis of the spent solution collected in WESP.